Islamic Republic of Mauritania : First Review Under the Extended Credit Facility Arrangement-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2018)
This paper discusses Mauritania's First Review Under the Extended Credit Facility (ECF) Arrangement. The outlook is positive, although considerable challenges remain to achieve high and inclusive growth. Vulnerabilities remain elevated and sustained reforms are needed to entrench macroeconomic stability; achieve inclusive growth that creates employment and reduces poverty; and improve the business climate and governance. Policy implementation has been satisfactory and the program is on track. All end-December 2017 performance criteria and eight of the ten structural benchmarks for December 2017-March 2018 were met; the remaining two were implemented with a one-month delay. The IMF staff recommends completion of the first review under the three-year ECF arrangement.